Think like an entrepreneur, act like a CEO : 50 indispensable tips to help you stay afloat, bounce back, and get ahead at work - Jones, Beverly E. (Career Press, 2016)
Education plus experience once guaranteed a successful career, but no more! Today, success depends on your ability to adapt. You must be agile, willing to adjust your professional expectations, and able to respond quickly to opportunities and threats. In this book you will learn practical ways to handle vexing workplace challenges. Each chapter uses true stories to illustrate the answers to common questions, including: how to leave your old job smoothly and start your new one with confidence and flair; how to gracefully accept praise for your work; how to recover from stress, setbacks, or the upheaval of a major project; how to stay steady in the midst of endless change. It's not enough to know how to manage common work-life challenges; you must also deal with the uncommon ones. --